Modulação de julgamentos morais e da satisfação com a vida após treinamento de meditação na compaixão - Cardille, Maurício (2019)
Moral judgments and compassion are objects of constant research, at various times, in the most diverse and wide areas of knowledge. Based on the existence of different moral matrices, which diverge in the emphasis of some moral foundations (justice, care, fidelity, respect, purity and liberty), there are many conflicts between people and groups because of these distinctions. Some factors capable of interfering in moral judgments vary from physiological, cognitive, social elements to emotional states. Compassion is one of the emotions with the greatest potential promoter of cooperation in prosocial attitudes. It occurs in situations where suffering, physical or emotional, concentrates attention and leads to an assessment of the possibilities of mitigating or eliminating pain; expressing a response in order to minimize or extinguish such suffering. Several recent researches has shown that the capacity for compassion can be developed through meditative practices. Such practices have the potential to generate benefits in wellbeing, health and even neuronal plasticity. In addition, compassion has intrinsically presents a property of judgment about the responsibility of the vulnerable individual over their own suffering and their practice has demonstrated activation of brain regions correlated with those activated in the tasks of moral judgment. Therefore, we evaluated the effects of cognitive-based compassion training (CBCT) for eight weeks on compassion, modulation of moral judgments, and satisfaction with life. This study included healthy adults (n = 62), aged between 18 and 35 years. The experimental group presented a significant difference with increased indices of compassion, satisfaction with life and the moral foundation of loyalty. There was also a significant difference demonstrating greater tolerance for dictatorial or abusive behavior on freedom of opinion or decision making. These results are similar those of other studies that evaluate the effect of these trainings on well-being and compassionate capacity and inspire further research on their impact on moral judgments.